Analisis Perilaku Masyarakat di Kawasan Konservasi Cagar Alam Gunug Sibela Halahera Selatan Provinsi Maluku Utara - Ade Haerullah; Said Hasan (Universitas Syiah Kuala, 2010)
This research was done in wild life conservation area of Sibela mountain, South Halmahera Regency, North Maluku Province from November 2009 to February 2010. The purpose of the research is to give evidence about how is the people’s behavior towards the wild life conservation area of Sibelia Mountain, the. The population of the research was all of patriarchs in three villages: Sawadai village, Tuokona and Gandasuli village. Furthermore, 46-47 people are chosen randomly from each village to get 140 patriarchs of total sample. Questionnaire instrument was used to collect the data. Questionnaire instrument and closed response interview guideline were used to collect the data of people’s behavior toward the wild life area conservation. Prior to distribute the instrument to the respondents, a test is carried out to the people who live in east Halmahera wild life area excluding from the research sample to get its validity and reliability. The result of analysis on people’s behavior in three different villages living in wild life area shows that they still have a low level of land utilization (about 20% - 25%). This result indicates that respondents who answered the questions of utilize of the conservation area tend to be in small number. This result also shows that the people of the three villages are having a tendency to do activities that caused environmental damage (contra conservation). The analysis result on people’s behavior in maintaining wild life conservation area of Sibela Mountain is also at a low level. From the three villages, the percentages are 8% - 13%. It indicates that people’s behavior tendency of maintaining or preserve the conserved area is at a very low level.